2020
DOI: 10.1155/2020/7103251
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight, Obesity Perception, and Actions to Achieve Desired Weight among Rural and Urban Ghanaian Adults

Abstract: Background. Accurate body weight perception is important to maintaining an ideal body weight. In Africa, a preference for a larger body size and its association with health and wellbeing has been well documented. It remains speculative if these perceptions have changed or improved and if differences exist among rural and urban dwellers. The main aim of this study was to assess the body weight and obesity perceptions among rural and urban Ghanaians. Methods. This cross-sectional study involved 565 participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
4
22
1
Order By: Relevance
“…Thus, women who are employed with long working hours were found to be obese. The results of this study are consistent with previous studies from Ghana [ 58 , 60 ], South Asian [ 51 , 52 , 55 ], and sub-Saharan Africa countries [ 2 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, women who are employed with long working hours were found to be obese. The results of this study are consistent with previous studies from Ghana [ 58 , 60 ], South Asian [ 51 , 52 , 55 ], and sub-Saharan Africa countries [ 2 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies conducted in other African countries, we found that South African women of childbearing age who attained secondary or higher education were more likely to be overweight/obese, similar to studies from Ghana [ 58 , 60 ], Bangladesh [ 52 , 53 ], and Ethiopia [ 6 , 40 , 67 ]. The likely reasons for this study finding in Nigeria and South Africa are that women with higher education are more likely to have a higher socio-economic status and material resources and have ready access to energy-dense nutrition and sugary beverages, as well as a more sedentary paying job.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The increase in obesity rate and frequency are related to many causes like socioeconomic status, married life, and other lifestyle factors. [ 2 3 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%